Silicon carbide biotechnology : a biocompatible semiconductor for advanced biomedical devices and applications - Saddow, Stephen E. (Elsevier, 2016)
Silicon Carbide Biotechnology: A Biocompatible Semiconductor for Advanced Biomedical Devices and Applications, Second Edition, provides the latest information on this wide-band-gap semiconductor material that the body does not reject as a foreign (i.e., not organic) material and its potential to further advance biomedical applications. SiC devices offer high power densities and low energy losses, enabling lighter, more compact, and higher efficiency products for biocompatible and long-term in vivo applications, including heart stent coatings, bone implant scaffolds, neurological implants and sensors, glucose sensors, brain-machine-interface devices, smart bone implants, and organ implants. This book provides the materials and biomedical engineering communities with a seminal reference book on SiC for developing technology, and is a resource for practitioners eager to identify and implement advanced engineering solutions to their everyday medical problems for which they currently lack long-term, cost-effective solutions.